An exploratory analysis of MR-guided fractionated stereotactic radiotherapy in patients with brain metastases. (May 2023) - Ding, Shouliang; Liu, Biaoshui; Zheng, Shiyang; Wang, Daquan; Liu, Mingzhi; Liu, Hongdong; Zhang, Pengxin; Peng, Kangqiang; He, Haoqiang; Zhou, Rui; Guo, Jinyu; Qiu, Bo; et al.
Highlights: The study evaluated the feasibility and benefits of online adaptive MR-guided FSRT in patients with brain metastases. Online adaptive MR-guided FSRT resulted in adequate target coverage and OAR sparing in patients with brain metastases. Significant inter-fractional changes could be found during FSRT in brain metastases patients treated by the 1.5 T MR-Linac. Abstract: Purpose: To assess the feasibility and potential benefits of online adaptive MR-guided fractionated stereotatic radiotherapy (FSRT) in patients with brain metastases (BMs). Methods and materials: Twenty-eight consecutive patients with BMs were treated with FSRT of 30 Gy in 5 fractions on the 1.5 T MR-Linac. The FSRT fractions employed daily MR scans and the contours were utilized to create each adapted plan. The brain lesions and perilesional edema were delineated on MR images of pre-treatment simulation (Fx0) and all fractions (Fx1, Fx2, Fx3, Fx4 and Fx5) to evaluate the inter-fractional changes. These changes were quantified using absolute/relative volume, Dice similarity coefficient (DSC) and Hausdorff distance (HD) metrics. Planning target volume (PTV) coverage and organ at risk (OAR) constraints were used to compare non-adaptive and adaptive plans. Results: A total of 28 patients with 88 lesions were evaluated, and 23 patients (23/28, 82.1%) had primary lung adenocarcinoma. Significant tumor volume reduction had been found during FSRT compared to Fx0 for all 88 lesions (median −0.75%, −5.33%, −9.32%, −17.96% and −27.73% at Fx1, Fx2, Fx3, Fx4 and Fx5, p  < 0.05). There were 47 (47/88, 53.4%) lesions being accompanied by perilesional edema and the inter-fractional changes were significantly different compared to those without perilesional edema ( p  < 0.001). Patients with multiple lesions (13/28, 46.4%) had more significant inter-fractional tumor changes than those with single lesion (15/28, 53.6%), including tumor volume reduction and anatomical shift ( p  < 0.001). PTV coverage of non-adaptive plans was below the prescribed coverage in 26/140 fractions (19%), with 12 (9%) failing by more than 10%. All 140 adaptive fractions met prescribed target coverage. The adaptive plans also had lower dose to whole brain than non-adaptive plans ( p  < 0.001). Conclusions: Significant inter-fractional tumor changes could be found during FSRT in patients with BMs treated on the 1.5 T MR-Linac. Daily MR-guided re-optimization of treatment plans showed dosimetric benefit in patients with perilesional edema or multiple lesions.